O universo passional do ator André em cenas de Lavoura Arcaica - Rochóli, Elisangela Aparecida Batarra (2008)
The novel Lavoura Arcaica by Raduan Nassar is this research object of analysis. This work tells the story of a family of Lebanese immigrants, reported through André’s point of view, the prodigal son who is away from the family due to the passion he has for his sister Ana. We analyze some enunciative scenes in the text, which occur before and after the incest between the siblings, in order to describe the state of mind of the actor André in his affective involvement with his relatives. The theory on which our research is based is the semiotics of the French school, with emphasis on the study of the passions which are of interest as they work as meaning effects inscribed and codified in the language. Therefore, through the expressive tone of André’s discourse, we can observe that this actor is a sensitive subject who expresses his anguish, pain and resentment, and in many moments is led by his anger whose canonical schema is described in some scenes of the text. We have also emphasized the description of the trajectories and figurative isotopies which are present in André’s discourse, observing how the figurativity is built in a text as regards the passions which appear in the text. This way, we have noted how the figurative investment of André’s suffering presents, in Nassar’s text, a semantic coherence which makes it closer to the poetic narration and moves the enunciatee to the sensitive appearance of the actor. Keywords: Semiotics, passions, anger, figurativity, isotopy.